From “bread and peace” revolts to politics of organization and communication: women in the Russian revolution - de Miguel Álvarez, Ana; Palomo Cermeño, Eva (Historia y Comunicación Social, 2018)
A revolution needs of good communication. This was Lenin’s idea and for this purpose he started several publications. Bolchevik women also had their own means of communication: Rabotnitsa. This paper analyzes different aspects of the communication policy regarding the cliché “Women and the Russian Revolution”. Beyond providing a list of “famous women” or describing their role in the pre and post revolutionary events, analytical keys are exposed in order to explore the communication process in terms of the sense of Revolution for women and the sense of women for Revolution. What messages were intended to be conveyed inside and outside the country, in the level of internal and external attraction, towards the international community? Finally, there is a reflection on how communication on this issue has been managed in the recent celebration of the centenary of the Russian Revolution.
Keywords: Russian Revolution; Bolchevik feminism; social movements; gender and history.